GILBERT'S SYNDROME- A CONCEALED ADVERSITY FOR PHYSICIANS AND SURGEONS - Rasool, Ahsan; Sabir, Sabir; Ashfaq, Muhammad; Farooq, Umer; Khan, Muhammad Zatmar; Khan, Faisal Yousaf (Journal of Ayub Medical College Abbottabad, 2015)
Gilbert's syndrome (often abbreviated as GS) is most common hereditary cause of mild unconjugated (indirect) hyperbilirubinemia. Various studies have been published depicting clinical and pharmacological effects of Gilbert's syndrome (GS). However GS as a sign of precaution for physician and surgeons has not been clearly established. A systematic study of the available literature was done. Key words of Gilbert's syndrome, hyperbilirubinemia and clinical and pharmacological aspects of GS were searched using PubMed as search engine. Considering the study done in last 40 years, 375 articles were obtained and their abstracts were studied. The criterion for selecting the articles for through study was based on their close relevance with the topic. Thus 40 articles and 2 case reports were thoroughly studied. It was concluded that Gilbert's syndrome has immense clinical importance because the mild hyperbilirubinemia can be mistaken for a sign of occult, chronic, or progressive liver disease.GS is associated with lack of detoxification of few drugs. It is related with spherocytosis, cholithiasis, haemolytic anaemia, intra-operative toxicity, irinotecan toxicity, schizophrenia and problems in morphine metabolism. It also has profound phenotypic effect as well. The bilirubin level of a GS individual can rise abnormally high in various conditions in a person having Gilbert's syndrome. This can mislead the physicians and surgeons towards false diagnosis. Therefore proper diagnosis of GS should be ascertained in order to avoid the concealed adversities of this syndrome.